Enablers and barriers to adopt the locally developed Masi mechanical ventilator amid COVID-19 pandemic in Peru - Montero, S.; Morón, G.; Arrunategui-Salas, G.; Casado, F.; Castañeda, B.; Salmón-Mulanovich, G. (Elsevier, 2023)
Limited supply of resources during the COVID-19 emergency encouraged the local development of the Masi mechanical ventilator (MV). Despite the efforts to promote Masi, adopting this innovation faced multiple obstacles, regardless of its performance. We explored the perceptions among healthcare personnel towards incorporating Masi to provide ventilatory support to COVID-19 patients during the second wave in Peru (January to June 2021).
Keywords: COVID-19; ARDS; Mechanical ventilators; Biomedical technology; Emergency care; Adoption; Qualitative research; https://purl.org/pe-repo/ocde/ford#3.02.08